Fish and invertebrate diversity at coral reef of Talang-Talang Island, Sematan, Sarawak - Nurrin Nabilah Teoh, Binti Ali Teoh (Universiti Malaysia Sarawak (UNIMAS), 2012)
This study was carried out in July 20 II and April 2012 to determine the abundance and diversity of fish and invertebrates at the natural reef of Talang-Talang Island. Data were collected using belt transect technique method with the aid of self-contained underwater breathing apparatus (SCUBA) and underwater visual censu es (UVC). Transect lines were laid 100 m parallel to the shore, with depth ranging between 3 -10m. Survey carried out covered a distance of 2.5 m from both sides of the transect line or a total area of 250 m2. Data collected were recorded with the aid of underwater slate, underwater flash card to aid in identification, and underwater camera. A total of 73 individuals of invertebrates were recorded at the study area representing 2 families and 3 species. Results show that species richness among the three stations ranged from 0.3899 at station 3 to 0.4969 at station I. A total of 18 genera and 22 species from a total number of 860 individuals of t1sh were documented. Results show that species richness among the three stations ranged from 2.2 171 at station I to 3.2633 at station 2. The assemblages of reef fish in coral reef ecosystem are affected by the percentage of live coral cover and feeding behavior of tishes. The population of invertebrate is affected by the overall condition of the coral reef.